The potential of Tinorian River as an eco-tourism spot in the Province of Iloilo, Philippines - Padojinog, G.G.; Dolor, J.B.; Garcia, M.D.; Monsale, F.N.; Baltazar, M.H.; Jolito, E.B.; Bedonia, J.B.; Poblete, S.F.B.; Villaluz, E.A.; Savillo, I.T. (Journal of Wetlands Ecology, 2011)
Tinorian River of Barotac Nuevo, Iloilo Philippines is teeming with natural life. Various avifauna species were seen including those that are common and non- migrating. The predominant species are the little egret, Egretta garzetta and the maritime kingfishers, Todiramphus chloris whose sizes are remarkably bigger compared to its inland counterparts. This maybe attributed to the rich source of riverine food primarily crustaceans and fishes. Outwards towards the sea, in mangrove studded islet, a small population of the huge Egretta alba could be found roosting. The mangrove bounded-river starts in a snake- like contour until it widens into a vast area surrounding islets of varying sizes in its midst. A tourist can devote his time leisurely kayaking in a banca or taking a ride in a motorized boat to explore the aesthetic beauty of this river all throughout its length. The small but very few family to single nipa huts can be seen in its banks as well as modified shelters of fishermen on floating rafts. This river is also a good source of fresh oysters and green mussels. Coupled with the silence of the mileu and the coolness of the air, once fully developed in an ecologically friendly manner, this could be a potential ecotourism spot. Key words: Ecotourism spot; avifauna; mangroves; commodity DOI: http://dx.doi.org/10.3126/jowe.v5i0.5621 J Wet Eco 2011 (5): 79-82